ANALISIS USABILITY WEBSITE SISTEM INFORMASI AKADEMIK STMIK KHARISMA MAKASSAR MENGGUNAKAN USE QUESTIONNAIRE - Widiawati, Melisa; Muawwal, Ahyar; Pontoh, Zaenab (KHARISMA Tech, 2023)
The Academic Information System Website of STMIK Kharisma Makassar is one of the website-based services on the internet owned by STMIK Kharisma Makassar which provides services for students such as purchasing Study Plan Cards (KRS), knowing the Semester Achievement Index (IPS), and registering payments. The Academic Information System Website of STMIK Kharisma Makassar has been implemented since 2017, but during its implementation there has been no benchmark to determine the level of satisfaction and usability of the system so that this study aims to analyze the usability of the Kharisma Makassar Academic Information System Website using the USE Questionnaire method in order to help the campus service process become better and become a basis for development. The USE Questionnaire method has 4 parameters, namely usefulness, easy of use, easy of learning, and satisfaction. Based on the results of the study, on the 3 features analyzed, the KRS selection feature gets a percentage of 72.13%, while the IPS graph feature is 70.91% and the payment registration feature is 70.41%. Based on the results of the average usability measurement of the 3 features, the results of the usability measurement of the Academic Information System website of STMIK Kharisma Makassar are 71.21% with a usability feasibility category that is feasible.